2018
DOI: 10.1136/vr.104280
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes associated with 13 cases of triceps tendon disruption in dogs and cats (2003–2014)

Abstract: This study reports data from a larger number of cases of triceps tendon disruption. Records from 10 veterinary referral hospitals between 2003 and 2014 were searched for canine and feline cases diagnosed with triceps tendon disruption, based on orthopaedic examination confirmed during surgery. Long-term follow-up and owner satisfaction were assessed using a questionnaire. There were 13 cases of triceps tendon disruption diagnosed across seven hospitals (nine dogs, four cats). Trauma, history or presence of a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…ESF, as chosen in this cat, is the preferred mode of transarticular fixation in small animals for supporting tendon (4, 5) and ligament injuries (4, 6, 7). Further, it supports the primary implants for fractures (6,8) of various joints, such as the stifle (4, 9-14), tarsal (5, 7, 10), and elbow (15). In particular, since the trans-articular fixation using ESF preserves the joint during the procedure (4-8), it is valuable for temporary immobilization of the associated joint without the articular invasion.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…ESF, as chosen in this cat, is the preferred mode of transarticular fixation in small animals for supporting tendon (4, 5) and ligament injuries (4, 6, 7). Further, it supports the primary implants for fractures (6,8) of various joints, such as the stifle (4, 9-14), tarsal (5, 7, 10), and elbow (15). In particular, since the trans-articular fixation using ESF preserves the joint during the procedure (4-8), it is valuable for temporary immobilization of the associated joint without the articular invasion.…”
Section: Discussionmentioning
confidence: 70%
“…Another major concern was postoperative degenerative changes of the femoral head, possibly due to immobilization of the hip joint and ischemic osteonecrosis secondary to reduced blood supply. Joint immobilization is the most significant cause of degenerative joint disease associated with trans-articular ESF (11,15,20), but it was not considered the primary cause of femoral head degeneration in this cat. Previous experimental and clinical studies have reported that prolonged joint immobilization alters the biochemical characteristics of synovial joints (3,20), inducing softening of the articular cartilage and decreasing cartilage thickness, leading to the development of degenerative joint disease (10,14).…”
Section: Discussionmentioning
confidence: 93%
“…25 Early and colleagues reported that transarticular external skeletal fixation and spica splints to be the most commonly applied measure of elbow immobilization following triceps tendon repair in dogs and cats respectively. 1 A spica splint was used successfully for support of the primary tendon reconstruction in this patient, immobilizing the limb in anatomical position to facilitate early weight bearing and protect the repair by avoiding excessive tension at the suture site. Furthermore, the surgeon did not want transarticular external skeletal fixation pin tracts in the region of the non-vascularized graft for potential increased risk of infection.…”
Section: Discussionmentioning
confidence: 97%
“…Disruption to the triceps brachii tendon is a rarely reported tendon injury in companion animals, with most triceps tendon disruptions secondary to avulsion. 1 Treatment outcomes have been limited to only a few descriptive studies in dogs. [2][3][4][5][6][7][8][9][10] This report describes successful treatment of a chronic complete laceration of the triceps brachii tendon in a 38 kg entire male German Shepherd.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to generalize regarding the required period of immobilization. Indeed, based on clinical experience, the duration of immobilization after triceps tendon repair in dogs mostly ranges from 4 to 8 weeks [ 8 ]. In addition, chronicity of the avulsion can affect the process of healing of tendon to bone, which may require prolonged immobilization, as in the case reported by Ambrosius and colleagues which required a 12-week immobilization period [ 13 ].…”
Section: Discussionmentioning
confidence: 99%